PENGENDALIAN KUALITAS PRODUK PIRING MELAMIN DENGAN METODE SIX SIGMA DI PT SEMESTA RAYA ABADI JAYA - & Minto Waluyo, Hadi Syamsudin, Didi Samanhudi, (JURNAL TEKMAPRO, 2015)
AbstractThis research was made based on the existing problems in the melamine company PT. Abadi Jaya Raya universe, namely the frequent occurrence of product defects or problems it defect. made this study by using the SIX SIGMA method. The purpose of this study was to determine the factors causing defect and propose improvements to reduce defects. Data from this study were drawn based on the number of defects during the month of January 2014 - June 2014. And the object of this research is a type of crown glass. The variables used are divided into 3 independent variables, including production data, the data of disability, type of disability.While the dependent variable is the increase in quality. With SIX SIGMA approach then be controlled by analyzing the causes of disability with fishbone diagram obtained factors cause defects there are 5 factors, human factors, factors machines, factor method, material factors, and environmental factors and based on the obtained data processing defects occur most commonly in January and CTQ most defects are Gupil.dan DPMO greatest value artifacts in april that 22500 were convertedi sigma at 3,451 and the proposed improvements to reduce the defect is FMEA.Keywords: Metode Six Sigma ,DMAIC, defectAbstrakPenelitian ini dibuat berdasarkan permasalahan yang ada di perusahaan PT. Semesta Raya Abadi Jaya, yaitu sering terjadinya produk cacat atau defect.Berdasarkan permasalahan tersebut maka dibuatlah penelitian ini dengan menggunakan metode six sigma Tujuan dari penelitian ini adalah mengetahui faktor âfaktor penyebab defect dan memberikan usulan perbaikan untuk menurunkan defect. Data dari penelitian ini diambil berdasarkan jumlah defect selama bulan Januari 2014 â Juni 2014. Dan objek dalam penelitian ini adalah piring melamin. Variabel-variabel yang digunakan terbagi menjadi 3 variabel bebas, antara lain data produksi, data kecacatan, jenis kecacatan. Sedangkan variabel terikatnya adalah peningkatan kualitas. DenganÂ  metode six sigma kemudian dilakukan pengendalian dengan menganalisa penyebab kecacatan dengan fishbone diagram didapat faktor faktor penyebab defect ada 5 faktor yaitu faktor manusia, faktor mesin, faktor metode, faktor material,dan faktor lingkungan dan berdasarkan pengolahan data didapat defect paling banyak terjadi pada bulan januari dan CTQ paling banyak defect adalah Gupil.dan nilai DPMO paling besar tedapat pada bulan april yaitu 225500 yang dikonversikan ke nilai sigma sebesar 3,451 dan usulan perbaikan untuk menurunkan defect adalah menggunakan FMEA.Kata Kunci : Metode Six Sigma ,DMAIC, defectAbstractThisÂ researchÂ wasÂ madeÂ basedÂ onÂ theÂ existingÂ problemsÂ inÂ theÂ melamineÂ companyÂ PT.Â AbadiÂ JayaÂ RayaÂ universe,Â namelyÂ theÂ frequentÂ occurrenceÂ ofÂ productÂ defectsÂ orÂ problemsÂ itÂ defect.Â madeÂ thisÂ studyÂ byÂ usingÂ theÂ SIXÂ SIGMAÂ method.Â TheÂ purposeÂ ofÂ thisÂ studyÂ wasÂ toÂ determineÂ theÂ factorsÂ causingÂ defectÂ andÂ proposeÂ improvementsÂ toÂ reduceÂ defects.Â DataÂ fromÂ thisÂ studyÂ wereÂ drawnÂ basedÂ onÂ theÂ numberÂ ofÂ defectsÂ duringÂ theÂ monthÂ ofÂ JanuaryÂ 2014Â -Â JuneÂ 2014.Â AndÂ theÂ objectÂ ofÂ thisÂ researchÂ isÂ aÂ typeÂ ofÂ crownÂ glass.Â TheÂ variablesÂ usedÂ areÂ dividedÂ intoÂ 3Â independentÂ variables,Â includingÂ productionÂ data,Â theÂ dataÂ ofÂ disability,Â typeÂ ofÂ disability.WhileÂ theÂ dependentÂ variableÂ isÂ theÂ increaseÂ inÂ quality.Â WithÂ SIXÂ SIGMAÂ approachÂ thenÂ beÂ controlledÂ byÂ analyzingÂ theÂ causesÂ ofÂ disabilityÂ withÂ fishboneÂ diagramÂ obtainedÂ factorsÂ causeÂ defectsÂ thereÂ areÂ 5Â factors,Â humanÂ factors,Â factorsÂ machines,Â factorÂ method,Â materialÂ factors,Â andÂ environmentalÂ factorsÂ andÂ basedÂ onÂ theÂ obtainedÂ dataÂ processingÂ defectsÂ occurÂ mostÂ commonlyÂ inÂ JanuaryÂ andÂ CTQÂ mostÂ defectsÂ areÂ Gupil.danÂ DPMOÂ greatestÂ valueÂ artifactsÂ inÂ aprilÂ thatÂ 22500Â wereÂ convertediÂ sigmaÂ atÂ 3,451Â andÂ theÂ proposedÂ improvementsÂ toÂ reduceÂ theÂ defectÂ isÂ FMEA.Keywords:Â MetodeÂ SixÂ SigmaÂ ,DMAIC,Â defect Abstrak PenelitianÂ iniÂ dibuatÂ berdasarkanÂ permasalahanÂ yangÂ adaÂ diÂ perusahaanÂ PT.Â SemestaÂ RayaÂ AbadiÂ Jaya,Â yaituÂ seringÂ terjadinyaÂ produkÂ cacatÂ atauÂ defect.BerdasarkanÂ permasalahanÂ tersebutÂ makaÂ dibuatlahÂ penelitianÂ iniÂ denganÂ menggunakanÂ metodeÂ sixÂ sigma TujuanÂ dariÂ penelitianÂ iniÂ adalah mengetahuiÂ faktorÂ âfaktorÂ penyebabÂ defectÂ danÂ memberikanÂ usulanÂ perbaikanÂ untukÂ menurunkanÂ defect.Â DataÂ dariÂ penelitianÂ iniÂ diambil berdasarkanÂ jumlahÂ defectÂ selamaÂ bulanÂ JanuariÂ 2014Â âÂ JuniÂ 2014.Â DanÂ objekÂ dalamÂ penelitianÂ iniÂ adalah piringÂ melamin.Â Variabel-variabelÂ yangÂ digunakanÂ terbagiÂ menjadi 3 variabelÂ bebas,Â antaraÂ lain dataÂ produksi,Â dataÂ kecacatan,Â jenisÂ kecacatan.Â SedangkanÂ variabelÂ terikatnyaÂ adalah peningkatanÂ kualitas. DenganÂ Â metodeÂ sixÂ sigmaÂ kemudianÂ dilakukanÂ pengendalianÂ denganÂ menganalisaÂ penyebabÂ kecacatanÂ denganÂ fishboneÂ diagramÂ didapatÂ faktorÂ faktorÂ penyebabÂ defectÂ adaÂ 5Â faktorÂ yaituÂ faktorÂ manusia,Â faktorÂ mesin,Â faktorÂ metode,Â faktorÂ material,danÂ faktorÂ lingkunganÂ danÂ berdasarkanÂ pengolahanÂ dataÂ didapatÂ defectÂ palingÂ banyakÂ terjadiÂ padaÂ bulanÂ januariÂ danÂ CTQÂ palingÂ banyakÂ defectÂ adalahÂ Gupil.danÂ nilaiÂ DPMOÂ palingÂ besarÂ tedapatÂ padaÂ bulanÂ aprilÂ yaituÂ 225500Â yangÂ dikonversikanÂ keÂ nilaiÂ sigmaÂ sebesarÂ 3,451 danÂ usulanÂ perbaikanÂ untukÂ menurunkanÂ defectÂ adalahÂ menggunakanÂ FMEA.KataÂ KunciÂ :Â MetodeÂ SixÂ SigmaÂ ,DMAIC,Â defect